Delmar’s Standard Textbook of ELECTRICITY - Herman, Stephen L. (Cengage, 2012)
Understanding the theory and application of electrical concepts is necessary for a successful career in the electrical field specifically in industrial maintenance and installation, and this newly revised, full color text delivers! Delmar's Standard Textbook of Electricity, Fourth Edition trains aspiring electricians by blending concepts relating to electrical theory with practical 'how to' information that prepares readers for situations commonly encountered on the job. This revision retains all the hallmarks of our market-leading prior editions, but displays enhancements such as more practical application problems. Topics span the major aspects of the electrical field including direct and alternating current circuits, basic theory, transformers, generators, and motors. This new edition has been organized so that all relevant information is located within a given chapter which allows for flexibility to access and cover topics in any order making this text an indispensable resource.